EVIDENCE FROM CHARCOAL ANALYSIS FOR THE EXTENSIVE EXPLOITATION OF CORK-OAK (QUERCUS SUBER) FOREST IN THE ROMAN IMPERIAL PERIOD: THE VICUS OF THAMUSIDA (NW MOROCCO) - ALLEVATO, Emilia; PECCI, Alessandra; PAPI, Emanuele; Pasquale, Gaetano Di (Proceedings of the Fourth International Meeting of Anthracology, 2013)
This work shows the preliminary results of the study of charcoal collected in the vicus of Thamusida – Sidi Ali ben Ahmed (Morocco), in the Roman province of Mauretania Tingitana. The charcoal assemblage gives information on the woody flora and the wood usage during a period from the second half of the 1st cent. AD to the 3rd cent. AD, during the Roman occupation of the site. Data suggest the presence of a Quercus suber forest in the close surrounding of the site, with larger extension with respect to the present-day Mamora forest. The presence of Vitis vinifera and Olea europaea in the agrarian landscape was also detected. The presence within the charcoal assemblages of Castanea sativa it is worth to note since its presence in the wild vegetation in the surrounding of the site is rather improbable
The following values have no corresponding Zotero field: periodical: Proceedings of the Fourth International Meeting of Anthracology issue: September 2008
Keywords: CHARCOAL ANALYSIS; Firewood; Mamora forest; Roman imperial period; Timber

A multiproxy reconstruction of the palaeoenvironment and palaeoclimate of the Late Pleistocene in northeastern Iberia: Cova dels Xaragalls, Vimbodí-Poblet, Paratge Natural de Poblet, Catalonia - López-García, Juan Manuel; Blain, Hugues-Alexandre; Bennàsar, Maria; Euba, Itxaso; Bañuls, Sandra; Bischoff, James; López-Ortega, Esther; Saladié, Palmira; Uzquiano, Paloma; Vallverdú, Josep (Boreas, 2012)
The Cova dels Xaragalls is a small open karst system, located in the municipality of Vimbodí-Poblet (Tarragona, Catalonia, NE Spain). It is an important Holocene archaeological site that was inspected in the 1970s but from which little has been published. New excavations starting in 2008 have exposed a deep Late Pleistocene stratigraphical sequence. In this paper, we present for the first time palaeoenvironmental and palaeoclimatic reconstructions of this Late Pleistocene succession on the basis of both the small-vertebrate assemblages and the charcoals. Results from the small-vertebrate associations along the sequence indicate that the landscape had open-woodland habitats in the vicinity of the Cova del Xaragalls, with wet points in the surrounding area. Woodland habitats were dominant throughout the sequence, as evidenced by the abundance of the species Apodemus sylvaticus, but were better developed during warm periods (layers C5 and C8), whereas during cold periods (layers C4 and C3) the environment was slightly more humid in response to higher mean annual precipitation and the opening of the landscape. The charcoal analysis indicates that the woodland surrounding the cave was composed mainly of Pinus (more than 90% was identified as Pinus), but that during the cold period (C3–C4) it incorporated some Quercus ilex/coccifera and Angiosperm indet., probably linked with greater precipitation. Comparisons are made with other long palaeoenvironmental sequences from the northeastern Iberian Peninsula and with global marine isotopic curves, providing a scenario for the palaeoclimatic and palaeoenvironmental changes that occurred during the Late Pleistocene in the woodland areas surrounding the Cova dels Xaragalls.
Keywords: CHARCOAL ANALYSIS; Cova dels Xaragalls; Late Pleistocene; Open woodlands (voyant); palaeoclimatic changes; palaeoenvironmental changes; small-vertebrate assemblages

Environment and landscape management during the Middle Neolithic in Southern France: Evidence for agro-sylvo-pastoral systems in the Middle Rhone Valley - Delhon, Claire; Thiébault, Stéphanie; Berger, Jean-François (Quaternary International, 2009)
Rescue excavations in the Middle Rhone Valley have provided opportunities to develop innovative strategies for the study of palaeoenvironments. These strategies involve sampling and analysis of botanical remains, recovered not only from archaeological sites but also in ‘‘off-site’’ pedosedimentary sequences thought to be poor in botanical remains. Thus, these remains (phytoliths, pedocharcoal) give access to unexplored depositional contexts, such as alluvial plains. Moreover, off-site data are useful because they minimise the hazard of cultural bias (e.g., selection of species during wood gathering). Comparison of data collected in the alluvial plain with data obtained via anthracological analyses of karstic caves and rock-shelters in the hinterland suggests a complex agro-sylvopastoral management of the landscape during the Middle Neolithic. We propose a pattern that supposes considerable specialization in use of plains vs. slopes in the landscape, and a strong and continuous human pressure on the vegetation and soils between 4500 and 3500 cal BC. Nevertheless, these constraints are not sufﬁcient to explain the persistence of such a system for more than a millennium. Favourable climatic conditions are thought to have been a determining factor in the persistence of an ecologically meta-stable relationship between human societies and their natural environment.
Keywords: CHARCOAL ANALYSIS; Middle Neolithic; Middle Rhone; oak; vegetation dynamics (citation)

Environment and landscape management during the Middle Neolithic in Southern France: Evidence for agro-sylvo-pastoral systems in the Middle Rhone Valley - Delhon, Claire; Thiébault, Stéphanie; Berger, Jean-François (Quaternary International, 2009)
Rescue excavations in the Middle Rhone Valley have provided opportunities to develop innovative strategies for the study of palaeoenvironments. These strategies involve sampling and analysis of botanical remains, recovered not only from archaeological sites but also in ‘‘off-site’’ pedosedimentary sequences thought to be poor in botanical remains. Thus, these remains (phytoliths, pedocharcoal) give access to unexplored depositional contexts, such as alluvial plains. Moreover, off-site data are useful because they minimise the hazard of cultural bias (e.g., selection of species during wood gathering). Comparison of data collected in the alluvial plain with data obtained via anthracological analyses of karstic caves and rock-shelters in the hinterland suggests a complex agro-sylvopastoral management of the landscape during the Middle Neolithic. We propose a pattern that supposes considerable specialization in use of plains vs. slopes in the landscape, and a strong and continuous human pressure on the vegetation and soils between 4500 and 3500 cal BC. Nevertheless, these constraints are not sufﬁcient to explain the persistence of such a system for more than a millennium. Favourable climatic conditions are thought to have been a determining factor in the persistence of an ecologically meta-stable relationship between human societies and their natural environment.
Keywords: CHARCOAL ANALYSIS; Middle Neolithic; Middle Rhone; oak; vegetation dynamics (citation)

Climate versus human-driven fire regimes in Mediterranean landscapes: the Holocene record of Lago dell’Accesa (Tuscany, Italy) - Vannière, B; Colombaroli, D; Chapron, E; Leroux, A; Tinner, W; Magny, M (Quaternary Science Reviews, 2008)
A high-resolution sedimentary charcoal record from Lago dell’Accesa in southern Tuscany reveals numerous changes in fire regime over the last 11.6kyr cal.BP and provides one of the longest gap-free series from Italy and the Mediterranean region. Charcoal analyses are coupled with gamma density measurements, organic-content analyses, and pollen counts to provide data about sedimentation and vegetation history. A comparison between fire frequency and lake-level reconstructions from the same site is used to address the centennial variability of fire regimes and its linkage to hydrological processes. Our data reveal strong relationships among climate, fire, vegetation, and land-use and attest to the paramount importance of fire in Mediterranean ecosystems. The mean fire interval (MFI) for the entire Holocene was estimated to be 150yr, with a minimum around 80yr and a maximum around 450yr. Between 11.6 and 3.6kyrcal.BP, up to eight high-frequency fire phases lasting 300–500yr generally occurred during shifts towards low lake-level stands (ca 11,300, 10,700, 9500, 8700, 7600, 6200, 5300, 3400, 1800 and 1350cal. yrBP). Therefore, we assume that most of these shifts were triggered by drier climatic conditions and especially a dry summer season that promoted ignition and biomass burning. At the beginning of the Holocene, high climate seasonality favoured fire expansion in this region, as inmany other ecosystems of the northern and southern hemispheres. Human impact affected fire regimes and especially fire frequencies since the Neolithic (ca 8000–4000cal.yrBP). Burning as a consequence of anthropogenic activities becamemore frequent after the onset of the Bronze Age (ca 3800–3600cal. yrBP) and appear to be synchronous with the development of settlements in the region, slash-and-burn agriculture, animal husbandry, and mineral exploitation. The anthropogenic phases with maximum fire activity corresponded to greater sensitivity of the vegetation and triggered significant changes in vegetational communities (e.g. temporal declines of Quercus ilex forests and expansion of shrublands and macchia). The link between fire and climate persisted during the mid- and late Holocene, when human impact on vegetation and the fire regime was high. This finding suggests that climatic conditions were important for fire occurrence even under strongly humanised ecosystem conditions.
Keywords: CHARCOAL ANALYSIS; Climatic conditions; Fire regime; Holocene; human activities; Pollen analysis; Vegetation history (voyant)

Climate versus human-driven fire regimes in Mediterranean landscapes: the Holocene record of Lago dell’Accesa (Tuscany, Italy) - Vannière, B.; Colombaroli, D.; Chapron, E.; Leroux, A.; Tinner, W.; Magny, M. (Quaternary Science Reviews, 2008)
A high-resolution sedimentary charcoal record from Lago dell’Accesa in southern Tuscany reveals numerous changes in fire regime over the last 11.6kyr cal.BP and provides one of the longest gap-free series from Italy and the Mediterranean region. Charcoal analyses are coupled with gamma density measurements, organic-content analyses, and pollen counts to provide data about sedimentation and vegetation history. A comparison between fire frequency and lake-level reconstructions from the same site is used to address the centennial variability of fire regimes and its linkage to hydrological processes. Our data reveal strong relationships among climate, fire, vegetation, and land-use and attest to the paramount importance of fire in Mediterranean ecosystems. The mean fire interval (MFI) for the entire Holocene was estimated to be 150yr, with a minimum around 80yr and a maximum around 450yr. Between 11.6 and 3.6kyrcal.BP, up to eight high-frequency fire phases lasting 300–500yr generally occurred during shifts towards low lake-level stands (ca 11,300, 10,700, 9500, 8700, 7600, 6200, 5300, 3400, 1800 and 1350cal. yrBP). Therefore, we assume that most of these shifts were triggered by drier climatic conditions and especially a dry summer season that promoted ignition and biomass burning. At the beginning of the Holocene, high climate seasonality favoured fire expansion in this region, as inmany other ecosystems of the northern and southern hemispheres. Human impact affected fire regimes and especially fire frequencies since the Neolithic (ca 8000–4000cal.yrBP). Burning as a consequence of anthropogenic activities becamemore frequent after the onset of the Bronze Age (ca 3800–3600cal. yrBP) and appear to be synchronous with the development of settlements in the region, slash-and-burn agriculture, animal husbandry, and mineral exploitation. The anthropogenic phases with maximum fire activity corresponded to greater sensitivity of the vegetation and triggered significant changes in vegetational communities (e.g. temporal declines of Quercus ilex forests and expansion of shrublands and macchia). The link between fire and climate persisted during the mid- and late Holocene, when human impact on vegetation and the fire regime was high. This finding suggests that climatic conditions were important for fire occurrence even under strongly humanised ecosystem conditions.
Keywords: CHARCOAL ANALYSIS; Climatic conditions; Fire regime; Holocene; human activities; Pollen analysis; Vegetation history (voyant)

Man-Made Landscapes From the Third–Second Millennia Bc: the Example of Castelo Velho (Freixo De Numão, North-East Portugal) - Figueiral, Isabel; Jorge, Susana O (Oxford Journal of Archaeology, 2008)
The analysis of charred plant material from Castelo Velho (northeastern Portugal) yields information about the environmental background of a long-term architectural project. Work focuses on the physical characteristics of this sui generis site and on the interrelationships between human communities and their vegetal environment. Important vegetation changes are recorded despite the fact that site ‘occupation’is considered to be sporadic and therefore causing only minor anthropogenic impact. Evergreen oaks (Quercus, evergreen) dominate during the ﬁrst two stratigraphic layers but are replaced by the tree-strawberry (Arbutus unedo) during a third layer. This change may result from a premeditated woodland management, ensuring that the site remained visible in the distance. Special attention is given to the plant assemblage and broken pottery found in a sealed structure (layer 3) and thought to have served a ‘ritual’ purpose. Seeds of Triticum aestivum/ compactum are largely predominant.
Keywords: Arbutus unedo (voyant); CHARCOAL ANALYSIS; Evergreen oaks; vegetation changes

Man-Made Landscapes From the Third–Second Millennia Bc: the Example of Castelo Velho (Freixo De Numão, North-East Portugal) - Figueiral, Isabel; Jorge, Susana O. (Oxford Journal of Archaeology, 2008)
The analysis of charred plant material from Castelo Velho (northeastern Portugal) yields information about the environmental background of a long-term architectural project. Work focuses on the physical characteristics of this sui generis site and on the interrelationships between human communities and their vegetal environment. Important vegetation changes are recorded despite the fact that site ‘occupation’is considered to be sporadic and therefore causing only minor anthropogenic impact. Evergreen oaks (Quercus, evergreen) dominate during the ﬁrst two stratigraphic layers but are replaced by the tree-strawberry (Arbutus unedo) during a third layer. This change may result from a premeditated woodland management, ensuring that the site remained visible in the distance. Special attention is given to the plant assemblage and broken pottery found in a sealed structure (layer 3) and thought to have served a ‘ritual’ purpose. Seeds of Triticum aestivum/ compactum are largely predominant.
Keywords: Arbutus unedo (voyant); CHARCOAL ANALYSIS; Evergreen oaks; vegetation changes

Vegetation changes and human action from the Neolithic to the Bronze Age (7000–4000 BP) in Alicante, Spain, based on charcoal analysis - Badal, Ernestina; Bernabeu, Joan; VERNET, J. L. (Vegetation History and Archaeobotany, 1994)
Charcoal analysis reveals various palaeo-eco- logical phases from the Neolithic to the Bronze Age. Ag- riculture starts about 7000 B.P. in favourable ecological conditions. Most of the charcoal spectra from sites iin the coast represent thermomediterranean holm-oak forest; those from the inland mountains represent mesome- diterranean holm-oak forest. The Neolithic I Impressed Ware people were the first to clear the forest to plant their crops. This clearance of primary woodland resulted in the development of secondary vegetation of pine woods or scrub. The scrub reached its maximum during the Bell Beaker phase and Bronze Age in the Cova de les Cendres. In the Neolithic II open air sites, the percent- ages of Quercus ilex/coccifera remain high. This may be the result of a different exploitation of the land, or suit- able conditions for the growth and survival of the vegeta- tion.
Keywords: bronze; CHARCOAL ANALYSIS; human impact; Neolithic; Spain

CONTRIBUTION OF CHARCOAL ANALYSIS TO THE STUDY OF VEGETAL PALEOENVIRONMENT IN CATALONIA (SPAIN) - MORA, M T R (BULLETIN DE LA SOCIETE BOTANIQUE DE FRANCE-ACTUALITES BOTANIQUES, 1992)
Charcoal analysis of seventeen archaeological sites in Catalonia (north-east of Spain) gives an approach to the Holocenic vegetation history for this area. We establish four regionals patterns for the vegetation evolution : interior non continental, north-mediterranean, south-mediterranean and interior continental. We also notice the effects of anthropic action and the ancient distribution of particular species : Olea europeae, Fagus sylvatica, Pinus halepensis, Quercus suber.
Keywords: CHARCOAL ANALYSIS; REGIONAL PATERNS; vegetation history

HUMAN-PLANT RELATIONSHIPS DURING THE COPPER AND BRONZE AGES IN THE BAZA AND GUADIX BASINS (GRANADA, SPAIN) - ARIZA, M O R (BULLETIN DE LA SOCIETE BOTANIQUE DE FRANCE-ACTUALITES BOTANIQUES, 1992)
The anthracological study of six sites in the north of province of Granada (Spain) has uncovered vegetation for the Copper Age formed by a dense oak grove belonging to the association Rhamno-Quercetum cocciferae. In the Bronze Age, the intensification of agriculture caused changes in the vegetation, reflected in the anthracological diagrams by the increase in Pinus halepensis and the decrease of Quercus ilex-coccifera, as well a decline in the woodlands and an expansion of the legumes. The different species present in the vicinity of the site (or in a greater radius), servings such specific functions as the making of tools and utensils, house construction, and firewood for the hearth or for fours, give us preliminary insights into the ways in which these populations used space and their vegetal environment
Keywords: CHARCOAL ANALYSIS; COPPER AGE; Granada; Spain

Late glacial and Holocene vegetation of the Corbières based on charcoal analysis at the Cova de l'espérit (Salses, Pyrénées orientales, France) - Solari, Maria-Eugenia; Vernet, Jean-Louis (Review of Palaeobotany and Palynology, 1992)
Charcoal analysis from the end of the Würm Glaciation and the Holocene at Cova de l'Espérit reveals the coexistence, in the Corbières region, of thermo-and meso-Mediterranean taxa. Three principal paleoecological phases are described: the first corresponds to the Upper Paleolithic (Würm III), the period of maximum cold, dominated by Juniperus assemblages. The second phase includes levels from the end of the Mesolithic and early Neolithic. It shows the appearance of mesothermic species such as Buxus sempervirens, Acer sp. and Quercus ilex, at the same time as the development of a thermophilic suite of species e.g. Olea europaea, Rosmarinus officinalis and Pistacia. During this period, the effect of man on the environment remained slight. The third phase consists of the middle Neolithic and more recent periods and reveals the degradation of the environment due to the development of agriculture and animal husbandry. The Garrigue—a mediterranean open human-influenced vegetation—has persisted up to the present.
Keywords: CHARCOAL ANALYSIS; Cova de l'Espérit; Holocene; human influence; vegetation history (PG)

MEDITERRANEAN VEGETATIONS AND PREHISTORIC CIVILIZATIONS - THE CASE OF FONT-JUVENAL - THIEBAULT, S; Vernet, J L (BULLETIN DE LA SOCIETE BOTANIQUE DE FRANCE-ACTUALITES BOTANIQUES, 1992)
The Font-Juvenal thick stratigraphy allowed the identification of several thousand pieces of charcoals and gives vegetation assemblages very significant of the mediterranean forest evolution and human and environment relationship. Charcoal analysis results confirms the evolutiv pattern proposed and three periods are evidenced : the first one covers the early Neolithic and deciduous oak forest is prevalent; the second, during middle and recent Neolithics, puts out decreases in the oaks representation and an increase of Buxus and Ouercus ilex-coccifera. The third period, at the end of Neolithic, evidences the importance of Buxus and Quercus ilex-coccifera assemblages. The deciduous oak forest was the most important element of early Neolithic vegetal landscape. The gap between man and his environment is revealed by the presence of open areas taxa as Buxus and Quercus ilex-coccifera during the Chasseen.
Keywords: CHARCOAL ANALYSIS; mediterranean forest

La vegetation du bassin de l'aude, entre pyrenees et massif central, au tardiglaciaire et au postglaciaire d'apres l'analyse anthracologique - Vernet, Jean-Louis (Review of Palaeobotany and Palynology, 1980)
This study presents the first synthesis of the Late and Postglacial vegetation between the Pyrénées and the Massif Central, in the Aude Basin at lower elevation. The results are based upon the identification of more than 2,000 charcoal pieces from prehistoric settlements. Firs and pines (Pinus sylvestris) persist in the Pyrenean area as far as the Neolithic, contrary to the south of the Massif Central where a Mediterranean influence is recorded. Refuges of vegetation give the best explanation for Late Glacial phytogeography; evidence for these refuges has been found at Belvis. In the Mediterranean area we can describe three vegetation successions during Postglacial time. The early vegetation was dominated by pines and deciduous oaks (Preboreal, Boreal). Later deciduous oak forests with thermophilous plants were growing (Atlantic period). Finally, in the Subboreal and Subatlantic period evergreen oak forests (Quercus ilex) are extended. The late extension of Quercus ilex (Subatlantic or earlier) is of anthropic origin.
Keywords: CHARCOAL ANALYSIS; human influence (PG); Pyrenees; vegetation succession